Peran Perpustakaan IAIN Curup dalam Pengembangan Masyarakat Ilmiah Kampus - Rodin, Rhoni (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2018)
The purpose of this study was to determine and analyze how the role of IAIN Curup’s library in the development of the campus scientific community. This study uses a qualitative approach, with qualitative descriptive analysis. Data collection techniques with interviews, observation and documentation. The results of this study indicate that there are several things that have been done by the IAIN Curup’s Library to show its role in the development of the scientific community, namely providing e-resources; Online research skill training; form a library journal; hold regular FGD activities in the form of scientific discussions and knowledge sharing; and improvement of library facilities and infrastructure.